A Study on the Dynamic Mechanism of the Integration of Sports Tourism and Medical Tourism for Ethnic Minorities in Yunnan - Wenjie Yang, Ke Ren, Peng Wang (Forest Chemicals Review, 2022)
The feasibility of integrating sports tourism and medical tourism for ethnic minorities in Yunnan is analyzed through literature materials, field surveys and other research methods, and on this basis, the dynamic mechanism of their integration is explored, and it is finally concluded that the feasibility of integrating sports tourism and medical tourism for ethnic minorities in Yunnan lies in the significant medical value of ethnic minority sports tourism products, the sports tourism attributes of medical tourism, and the environmental advantages of most sports tourism regions in Yunnan. The dynamic mechanisms for the integration of the two are: high-quality medical care in ethnic minority sports tourism destinations with low prices and less waiting time; the psychological drive for pilgrimage of ethnic minorities and cross-border peoples; the objective demand of modern people for heterogeneous cultural experiences, etc.